Effect of inhaled steroids on clinical and inflammatory parameters in children with cystic fibrosis - KARADAĞ, BÜLENT TANER; HAKLAR, GONCAGÜL (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2017)
Background/aim: The effectiveness of inhaled corticosteroids (ICSs) in cystic fibrosis (CF) is controversial. The aim of this study was to investigate the effect of an ICS on bronchial hyperreactivity (BHR), oxidative status, and clinical and inflammatory parameters in CF patients. Materials and methods: CF patients were randomized to receive either 2 mg/day nebulized budesonide or 0.9% normal saline as placebo for 8 weeks. Results: Twenty-nine CF patients (mean age: 10.5 +/- 2.9 years) were enrolled in the study. There was no statistically significant difference between the two groups at the end of 8 weeks in terms of symptoms, pulmonary function, BHR, oxidative burst, hs-CRP, or ESR. Although there was a significant decrease in malondialdehyde levels in both groups, there was no difference between the two groups. Percentage of neutrophils in the sputum of patients decreased in the budesonide group (P = 0.006). Although sputum IL-8 levels significantly increased in both groups, there was no statistically significant difference between the two groups. Conclusion: Although there was a significant decrease in the percentage of neutrophils in sputum with budesonide, 8 weeks of 2 mg/day nebulized budesonide was not effective in terms of BHR, oxidative status, or clinical and other inflammatory parameters in children with CF.
Keywords: Antiinflammatory treatment; children; cystic fibrosis; glucocorticoids; inhalation; RANDOMIZED CONTROLLED-TRIAL; LUNG-FUNCTION DECLINE; FLUTICASONE PROPIONATE; ANTIINFLAMMATORY THERAPIES; AIRWAY INFLAMMATION; YOUNG-CHILDREN; LONG-TERM; CORTICOSTEROIDS; SPUTUM; METHACHOLINE